2013
DOI: 10.1002/ece3.630
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the cryptic invasion of a domestic conspecific: American mink in their native range

Abstract: Control of invasions is facilitated by their early detection, but this may be difficult when invasions are cryptic due to similarity between invaders and native species. Domesticated conspecifics offer an interesting example of cryptic invasions because they have the ability to hybridize with their native counterparts, and can thus facilitate the introgression of maladaptive genes. We assessed the cryptic invasion of escaped domestic American mink (Neovison vison) within their native range. Feral mink are a kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 63 publications
(132 reference statements)
3
20
0
Order By: Relevance
“…Development of effective management strategies is often hindered by lack of understanding about the population structure, including connectivity, specific routes of spread, relative roles of reproduction or immigration in sustaining local populations, and potential for interbreeding with native populations. Genetic tools provide a means of elucidating points of introduction, identifying hybridization with native relatives, as well as reconstructing routes of spread and assessing the relative roles of continued immigration versus reproduction in sustaining local invasive populations (Hampton et al 2004;Lecis et al 2008;Kidd et al 2009;Berry and Kirkwood 2010;Estoup and Guillemaud 2010;Sacks et al 2011;Beauclerc et al 2013;Fraser et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Development of effective management strategies is often hindered by lack of understanding about the population structure, including connectivity, specific routes of spread, relative roles of reproduction or immigration in sustaining local populations, and potential for interbreeding with native populations. Genetic tools provide a means of elucidating points of introduction, identifying hybridization with native relatives, as well as reconstructing routes of spread and assessing the relative roles of continued immigration versus reproduction in sustaining local invasive populations (Hampton et al 2004;Lecis et al 2008;Kidd et al 2009;Berry and Kirkwood 2010;Estoup and Guillemaud 2010;Sacks et al 2011;Beauclerc et al 2013;Fraser et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a successful introduction is hardly improbable just by smuggling only a few animals, especially when we consider the low rate of success of modern reintroduction-reinforcement campaigns (Põdra et al 2013a, b;. Even highly successful invaders as American mink have not been capable to establish in some areas where low number of individuals is introduced to the wild (Beauclerc et al 2013). Without doubt, capturing live mink and transporting them in the XIX century would have been expensive, and in order to be profitable we should expect a flourishing mink-fur industry to have developed in France, subsequent to the introduction, which was not the case.…”
Section: The Historic European Mink Distribution and Pitfalls Of Hypomentioning
confidence: 97%
“…Bowman et al (2007) first showed that the signature of escaping domestic mink could be detected across Canada in wild mink harvest data. Subsequently, studies in Ontario, Canada used genetic methods to document the extent of escaped domestic mink (Kidd et al 2009;Beauclerc et al 2013). For example, 78% of free-ranging mink sampled in the Niagara Falls area were either domestic or domestic-wild hybrids (Kidd et al 2009).…”
mentioning
confidence: 99%
“…The biotic effects of feral mink should differ somewhat in North America compared to other locations, owing to the occurrence of native conspecific mink. Sampling in Ontario has shown that escaped domestic mink hybridize with wild mink (Kidd et al 2009;Beauclerc et al 2013), which may lead to outbreeding depression due to a loss of local adaptation (Bowman et al 2007;Beauclerc et al 2013). An interface for potential pathogen transfer exists when there are lapses in biosecurity on mink farms.…”
mentioning
confidence: 99%
See 1 more Smart Citation